(untitled) (Jurnal Bakti Masyarakat Indonesia, 2019)
The Scientific Work Room which contains practical workbooks and student thesis in the XYZ faculty has not been well managed. The problem is that searching for books takes a long time and making the reports needed by the faculty cannot be fulfilled. These problems can be overcome by computerizing the management of the scientific works, so it is necessary to make a Scientific Paper Data Collection Application Program. Application program created is multi user, to be used by staff and users who need to search or borrow books. This application program can facilitate the search for students’ scientific works and also make reports required by the faculty. The application program was developed using the System Development Life Cicle (SDLC) methodology. The application program uses the My Sql database and PHP programming language. The application program has been installed in the Scientific Workspace and tested by the user using the UAT (User Acceptance Test) method. ABSTRAK: Ruang Karya ilmiah yang berisi buku kerja praktik dan buku skripsi mahasiswa di fakultas XYZ, belum dikelola secara baik. Masalah yang dihadapi adalah dalam pencarian buku membutuhkan waktu yang lama dan pembuatan laporan yang dibutuhkan fakultas belum dapat dipenuhi. Permasalahan tersebut dapat diatasi dengan melakukan komputerisasi pengelolaan buku karya ilmiah tersebut, sehingga perlu dibuat Program Aplikasi Pendataan Karya Ilmiah. Program Aplikasi yang dibuat multi user untuk digunakan oleh petugas dan user yang akan mencari/meminjam buku. Program aplikasi ini dapat mempermudah pencarian buku karya ilmiah mahasiswa dan juga pembuatan laporan-laporan yang dibutuhkan oleh fakultas. Program aplikasi dikembangkan dengan metodologi System Development Life Cicle (SDLC). Program aplikasi menggunakan basis data My Sql dan bahasa pemrograman PHP. Program aplikasi telah di-intstall di Ruang karya Ilmiah dan diuji oleh user menggunakan metode UAT ( User Acceptance Test).